Modeling of the α-lactalbumin and β-lactoglobulin protein separation - Rojas, E. E. G. (2011)
This work used the General Rate Model (GRM) to evaluate the experimental data of α-lactalbumin (α-la) and β-lactoglobulin (β-lg) mass transfer using size exclusion chromatography (SEC). The chromatographic simulation has become necessary in large scale production processes. Mathematical models have been used for the optimization and control of different operating conditions of the process, as well as providing calculations for the process scale-up. For the SEC experiments, the aqueous biphasic system was composed of polyethylene glycol 1500 g/mol, potassium phosphate and whey protein isolate. The polymeric phase was enriched with α-la and the saline phase with β-lg. The experiments were conducted using a glass column packed with the Shepadex G-25® gel. Both proteins were quantified by reverse phase liquid chromatography. The experimental data were fitted by non-linear regression, using the successive quadratic programming algorithm. The mass transfer model utilized represented adequately the SEC experimental results.